2019
DOI: 10.1002/jbm4.10131
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of the 6‐Minute Walk Test in Hypophosphatasia

Abstract: This investigation evaluated the reliability and validity of the 6‐Minute Walk Test (6MWT) in patients with pediatric hypophosphatasia (HPP). Children (aged 6 to 12 years; n = 11), adolescents (13 to 17 years; n = 4), and adults (18 to 65 years; n = 9) completed the 6MWT at screening and baseline in two clinical studies of asfotase alfa. Test‐retest reliability of the 6MWT, evaluated with Pearson's correlation coefficients ( r … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 60 publications
(141 reference statements)
0
12
0
4
Order By: Relevance
“…(25) Of the primary outcome measures of physical function (6MWT, TUG test, SPPB, and grip strength), both the 6MWT and the TUG test, as well as two of the three components of the SPPB, showed statistically significant improvements from baseline to sometime during 12 months of treatment, which indicates the effectiveness of asfotase alfa in improving the functional health of adult patients with pediatric-onset HPP. Minimum clinically important differences for adults with HPP have been established for the 6MWT (31 m) (26) ; in this study, the median 6MWT distance increased by a clinically meaningful 39 m at 6 months and 53 m at 12 months of treatment compared with baseline. Although improvements observed by 6 months were not significant, statistically significant improvements were noted at 12 months.…”
Section: Discussionmentioning
confidence: 76%
“…(25) Of the primary outcome measures of physical function (6MWT, TUG test, SPPB, and grip strength), both the 6MWT and the TUG test, as well as two of the three components of the SPPB, showed statistically significant improvements from baseline to sometime during 12 months of treatment, which indicates the effectiveness of asfotase alfa in improving the functional health of adult patients with pediatric-onset HPP. Minimum clinically important differences for adults with HPP have been established for the 6MWT (31 m) (26) ; in this study, the median 6MWT distance increased by a clinically meaningful 39 m at 6 months and 53 m at 12 months of treatment compared with baseline. Although improvements observed by 6 months were not significant, statistically significant improvements were noted at 12 months.…”
Section: Discussionmentioning
confidence: 76%
“…The 6MWT was used as a validated measure in combination with multiple exploratory tests, including the Bruininks-Oseretsky Test of Motor Proficiency (Running Speed and Agility subset and Strength subtest) for evaluating gross motor function, hand-held dynamometry for testing muscle strength of the hip extensors and abductors, the Lower Extremity Functional Scale to calculate the performance of transitional movements, locomotion, climbing stairs, and squatting, and the Brief Pain Inventory-Short Form for assessing pain [ 12 ]. Phillips et al also showed high test-retest reliability (r = 0.95; p < 0.0001) for the 6MWT in HPP as well as sufficient validity (i.e., walking distance increased as the severity of skeletal disease decreased) [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indicating the smallest benefit of value to the patient [ 14 ], the minimally clinically important difference (MCID) of the 6MWT is reportedly 31 m in adults with pediatric-onset HPP and 43 m in adolescents with pediatric-onset HPP [ 13 ]. In the present case, the 6MWT distance surpassed both MCID values: 48 m at 3 months of treatment and 102 m at 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…Dos 42 artigos, 27 eram estudos observacionais longitudinais 6,7,[9][10][11]13,[15][16][17][18][19][20]22,24,27,[29][30][31][35][36][37][38]40,41,43,45,46 , nove observacionais de corte transversal 14,21,23,25,26,39,42,44,47 e seis utilizaram dados de ensaios clínicos 8,12,28,[32][33][34] . Apenas três foram realizados com indivíduos hospitalizados, sendo um em sujeitos com lesão traumática cerebral 30 , outro em indivíduos durante ou fora do tratamento do câncer 40 e outro em sujeitos com doença renal terminal .…”
Section: Teste De Caminhada De Seis Minutos (Tc6)unclassified
“…Em relação à execução dos testes, foram realizados em corredores de 70 m 30,34 , 50 m 6 , 40 m 14,22,47 , 30 m 11,17,24,26,31,38,40,42,47 , 25 m 13,19,39 , 20 m 15,21,28,33,43,44 , 15 m 26,35 , 10 m 41 , 8 m 20 , um campo 40 m × 20 m 46 , em pista retangular 10 m x 50 m 41 , de 12 m x 6 m 30 , em corredor circular de 125 m 25 e em percurso oval de 150 e 250 pés 17 . Dezenove estudos seguiram as diretrizes da American Thoracic Society (ATS) 8,9,11,13,14,17,18,22,23,27,29,31,35,36,39,40,42,46,47 .…”
Section: Teste De Caminhada De Seis Minutos (Tc6)unclassified